ANALYSIS OF THE FEABILITY STUDY AND MARKETING MIX OF COFFEE BUSINESS IN OKU REGENCY SOUTH SUMATERA PROVINCE - Bursana, Bursana; Munajat, Munajat; Fifian, Fifian Permata Sari (International Journal of Social Science, 2024)
The coffee agro-industry has quite a big opportunity for development, where the prospects and market opportunities for the ground coffee business have many enthusiasts. South OKU Regency is the center for ground coffee MSMEs in South Sumatra. This research examines the marketing mix and development strategy for ground coffee businesses in South OKU Regency. This research was carried out in Mekakau Ilir District, South OKU Regency. The location determination was carried out purposively considering that Mekakau Ilir District, South OKU Regency is the coffee center in South Sumatra, especially South OKU. The research will be carried out in November 2023. The research method used is the survey method and the sampling method uses the census method where all those registered as coffee businesses in South OKU are taken as samples. There are 30 coffee business actors registered with the South OKU industry and trade service and all of them were taken as research samples. The results of the research show that the coffee business in South Oku Regency is feasible to operate with a feasibility level of the Net B/C value of 3.08 shows that the implementation of the coffee powder business which has been running for more than 5 years using an interest rate of 9.95% will provide a net profit of 3.08 double, which means that every investment made is equal to Rp. 1 money will produce a profit of Rp. 3.08, so that the ground coffee agro-industry activity is feasible to carry out.